Indonesian Strategic Leadership 5.0 Amidst Thucydides Trap (Dynamic System Approach) - Muhamad Noor Gibran; Jonni Mahroza; Afrizal Afrizal; Priyanto Priyanto; Sri Patmi; Fatwa Budiyanti; Lukman Yudho Prakoso (Mahesa Research Center, 2024)
The Indo-Pacific region is experiencing quite sharp conflicts. The power rivalry between these two countries also dragged Indonesia into Thucydides' trap because they joined an alliance with the aim of regional cooperation. This research aims to analyze the tendencies and projections of various aspects of the US vs China towards Indonesia in determining strategic leadership decisions 5.0. The method used is a dynamic system using 2018 time series data and projections up to 2050. The variables used by the Loewy Institute are Economic Relations, Defense Network, Diplomatic Influence, Cultural Influence, Economic Capability, Military Capability, Resilience, and Future Resources. The research results show that the model and tendencies of the US vs China rivalry are influenced by several factors. From 2018 to 2050, it is known that the US vs China rivalry shows fluctuating conditions. Novelty in this research includes 8 scenarios from (1) economic relations such as enhancing multilateral diplomacy and dialogue, promoting regional economic and security cooperation, (2)Defense Network such as strengthening economic, political, and security relations, (3)Diplomatic Influence such as diplomatic approach and regional cooperation, (4)Cultural Influence utilizing US cultural influence to strengthen diplomacy and international cooperation, (5)Economic Capability such as Indonesia can be an effective mediator between the US and China, (6)Military Capability such as strategic leadership 5.0 relies on diplomacy and coalitions, (7)Resiliance and (8)Future Resources such as effective mediator and promotes bilateral and multilateral cooperation. In conclusion, the US vs China rivalry will experience fluctuating developments.